Methodical Review of the Social and Economic Development Rankings of the Region Based on Primorsky Krai - Terenteva, Tatyana V.; Varkulevich, Tatyana V.; Vasilenko, Marina E.; Shumik, Ekaterina G.; Smitskih, Kseniya V. (International Review of Management and Marketing, 2016)
The article describes the use of the regional development ranking based on a separate territory of the Russian Federation. The Far East becomes the area of implementation of many major investment projects; therefore, the government is trying to attract foreign investors. In this paper, we purported to look how Primorsky Krai looks like from the perspective of a potential investor not familiar with the peculiarities of the policy of the Far Eastern Federal District Government; how the major infusions in the territory development affected its position in the major rankings, and to draw conclusions about the necessity and complexity of the rankings used. The authors have also examined the shortcomings of existing methods and proposed the ways for improving the evaluation methods used in the ranking system. Keywords: Primorsky Krai, ranking, development effectiveness, Free Port. JEL Classifications: Ð¡13, O10, O15, O16, O18.